2007
DOI: 10.1007/s10460-007-9082-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socio-economic and cultural factors in rice varietal diversity management on-farm in Nepal

Abstract: A questionnaire survey of 408 households explored the role of socio-economic and cultural factors in rice (Oryza sativa L.) varietal diversity management on-farm in two contrasting eco-sites in Nepal. Multiple regression outputs suggest that number of parcels of land, livestock number, number of rice ecosystems, agro-ecology (altitude), and use of chemical fertilizer have a significant positive influence on landrace diversity on-farm, while membership in farmersÕ groups linked to extension services has signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 21 publications
5
78
0
Order By: Relevance
“…Several previous case studies at the community level in Mexico (Perales et al, 2000;Perales et al, 2005;Latournerie-Moreno et al, 2006;Brush and Perales, 2007;Bellón and Hellin, 2011;Tuxill et al, 2010) and elsewhere (Brush, 2004;Guzman et al, 2005;Bisht et al, 2007;Rana et al, 2007;Jarvis et al, 2008;Bezançon et al, 2009;FAO, 2010;Jackson et al, 2010;Mulumba et al, 2012;Zimmerer, 2013) have demonstrated the persistence of landraces for climatic, ecological, cultural or social reasons. This trend is reaffirmed by the data from Mexico's national effort for maize diversity recollection (CONABIO, 2014).…”
Section: Longitudinal Analysis On Maize Varieties In Yucatan 57mentioning
confidence: 96%
“…Several previous case studies at the community level in Mexico (Perales et al, 2000;Perales et al, 2005;Latournerie-Moreno et al, 2006;Brush and Perales, 2007;Bellón and Hellin, 2011;Tuxill et al, 2010) and elsewhere (Brush, 2004;Guzman et al, 2005;Bisht et al, 2007;Rana et al, 2007;Jarvis et al, 2008;Bezançon et al, 2009;FAO, 2010;Jackson et al, 2010;Mulumba et al, 2012;Zimmerer, 2013) have demonstrated the persistence of landraces for climatic, ecological, cultural or social reasons. This trend is reaffirmed by the data from Mexico's national effort for maize diversity recollection (CONABIO, 2014).…”
Section: Longitudinal Analysis On Maize Varieties In Yucatan 57mentioning
confidence: 96%
“…(2006;Adnyana and Kariyasa, 2006;Mahananto et al, 2009;Malian et al, 2004) have all conducted research regarding Indonesia's various rice farming areas. Laborte et al (2015;Rana et al, 2007) and others have done research concerning rice farming outside of Indonesia. In our research we analyze the correlation between production factors, rice quality, rice price, production and farming income.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in order to improve Kersting's productivity and limit the extent of genetic loss, there is a need to undertake an extensive collection, characterization and evaluation of the available Kersting's groundnut germplasm. In so doing, varieties meeting both farmers and consumers' preferences or varieties with important traits to be exploited in breeding programs can be identified [67][68][69][70]. This will also be important to get useful information for the definition of core collection for conservation and materials sharing purposes among scientists.…”
Section: Threats and Conservation Statusmentioning
confidence: 99%